Comparison of Pregnancy and Neonatal Outcomes of Single Frozen Blastocyst Transfer Between Letrozole-Induction and HRT Cycles in Patients With Abnormal Ovulation - Zhang, Junwei; Li, Zhen; Sun, Lijun; Guan, Yichun; Du, Mingze (Frontiers in Endocrinology, 2021)
Background: The use of frozen embryo transfer (FET) cycles has dramatically risen. The optimal endometrial preparation method for women undergoing FET is of utmost importance to provide the optimal chances of pregnancy. For patients with abnormal ovulation in particular, there have been few studies on FET protocols; notably, most of these studies focus only on the clinical pregnancy rate or live birth rate (LBR) and pay little attention to the regimen’s safety for offspring. Methods: It was a retrospective cohort study. First FET cycle with a single blastocyst from whole embryo frozen IVF/ICSI at the Reproductive Center of Third Affiliated Hospital of Zhengzhou University between January 2016 and January 2020. The LBR was the primary outcome of interest. The secondary outcome measures were miscarriage rate and offspring safety, including preterm birth, low birthweight (LBW), small-for-gestational age (SGA), macrosomia and large-for-gestational age (LGA). Results: In total, 2782 FET cycles met the eligibility criteria for analysis. Additionally, there were 1178 singleton births from FET cycles. The clinical pregnancy rate was 58.4% in the L-FET group and 54.5% in the HRT group, with no statistical significance (P=.116). The miscarriage rate was higher in the HRT group than in the L-FET group (21.7% vs. 14.3%, P=.005). The LBR was significantly higher in the L-FET group than in the HRT group (49.6% vs. 41.7%, P=.001). Neonatal outcomes were similar between the two groups. After adjustments for confounding factors, the LBR was higher in the L-FET group (aOR 1.30, 95% CI 1.06-1.58). The rate of miscarriage was lower in the L-FET group (aOR 0.63, 95% CI 0.44-0.90). Conclusion: For patients with abnormal ovulation, the L-FET regimen has a higher LBR and lower miscarriage rate than HRT. The neonatal outcomes were similar between the two groups.